2020
DOI: 10.7441/joc.2020.03.01
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 Pandemic and the Antecedants for the Impulse Buying Behavior of US Citizens

Abstract: In an analysis based on the theory of Fear, this study examines impulse purchase patterns during the COVID-19 Pandemic across major US urban centers. Data from 889 US consumers were collected from leading US cities to evaluate impulse buying behavior fluctuations using SEM-based multivariate approaches to examine the survey statistics. We used COVID-19 as a moderating variable of this impulse purchase behavior. The results confirmed that Fear of a complete lockdown, peers buying, scarcity of essential products… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
143
2
16

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(173 citation statements)
references
References 30 publications
12
143
2
16
Order By: Relevance
“…In Mexico as well as throughout the world the negative effects of the pandemic have affected many areas, even today, new affectations are being found in health as well as in the economy, environment and the daily life of human beings. An example is that in the U.S. and the rest of the world, the pandemic caused by COVID-19 affected the consumer's purchasing decision, and spending more time at home seemed to lead to an impulsive purchasing behavior (Ahmed et al, 2020). The inventory purchases for the study's company increased significantly, but not precisely because of panic shopping, instead of that, they were purchases to supply an inventory to meet market demands, thus the domestic manufactured products increased.…”
Section: Discussionmentioning
confidence: 99%
“…In Mexico as well as throughout the world the negative effects of the pandemic have affected many areas, even today, new affectations are being found in health as well as in the economy, environment and the daily life of human beings. An example is that in the U.S. and the rest of the world, the pandemic caused by COVID-19 affected the consumer's purchasing decision, and spending more time at home seemed to lead to an impulsive purchasing behavior (Ahmed et al, 2020). The inventory purchases for the study's company increased significantly, but not precisely because of panic shopping, instead of that, they were purchases to supply an inventory to meet market demands, thus the domestic manufactured products increased.…”
Section: Discussionmentioning
confidence: 99%
“…Hypothetically, it can increase fear by disseminating pictures of the empty shelves and rumors of a shortage of supply (4,10,11,15). Previous studies revealed that mass media and social media have a role in disseminating fear and rumors, which in turn increases erratic behavior like PB (10,12,18,19). Furthermore, it has been reported that fake news on social media demonstrated a strong positive impact on impulse buying (18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that mass media and social media have a role in disseminating fear and rumors, which in turn increases erratic behavior like PB (10,12,18,19). Furthermore, it has been reported that fake news on social media demonstrated a strong positive impact on impulse buying (18)(19)(20). In contrast, mass media and social media can minimize PB by reducing public tension and threat and assuring the public that there is a sufficient supply of good.…”
Section: Discussionmentioning
confidence: 99%
“…Pochea et al ( 23) used quantile regression analysis as an estimation method, and found evidence of herding behavior in all central and Eastern European countries, except Poland and Romania: when the market rises, investors will follow each other in buying transactions, but when the market turns down, investors will not follow each other. Ahmed et al (24) used the multivariate method based on the structural equation model to study the data of 889 consumers and found that peer purchase and other factors had an important impact on the impulsive purchase mode. Zheng et al (25) pointed out that consumers tend to imitate others, and social media posts can play an important role in the diffusion of imitation and purchase behavior.…”
Section: Introductionmentioning
confidence: 99%